The influence of expatriate cultural intelligence on organizational embeddedness and knowledge sharing: The moderating effects of host country context - Sebastian Stoermer; Samuel Davies; Fabian Jintae Froese (Journal of International Business Studies, 2020)
This study advances our understanding of the contextualization of the effects of cultural intelligence (CQ). Drawing from trait activation theory and institutional theory, we develop a multi-level model showing how host countries' informal and formal openness towards foreigners facilitate or constrain the importance of expatriates' CQ in becoming embedded in the host organization. Furthermore, this study positions organizational embeddedness as a mediator in the association between expatriates' CQ and a central element of expatriates' jobs – knowledge sharing in the foreign workplace. Results from a cross-lagged survey of 1327 expatriates from 100 different nations residing in 30 host countries combined with secondary data indicate expatriate CQ relates positively to organizational embeddedness. Cross-level interaction analyses further suggest that in-group collectivism, the proxy for host countries' informal openness towards foreigners, facilitates the importance of CQ as a predictor of expatriates' organizational embeddedness. In contrast, CQ was not found to interact with the proxy for host countries' formal openness towards foreigners, i.e. national immigration policies. Consistent with predictions, we identified that CQ relates positively to knowledge sharing and that organizational embeddedness carries an indirect effect. We discuss the implications for theory and practice.
Keywords: 330; expatriate management; cultural intelligence; in-group collectivism; immigration policies; organizational embeddedness; knowledge sharing; trait activation theory; multi-level analysis